Distribuição da umidade no solo e do potencial matriarcal medido e estimado, usando-se linha-fonte com fluxo em regime permanente - Mota Ramos , Márcio; Afonso Ferreira , Paulo; Bernardo , Salassier; Vieira , Manoel (Revista Ceres, 2025)
Steady soil water flow from line sources was analysed using a linearized form of the moisture flow equation. Both single and parallel line sources at the soil surface were considered.